Concrete case studies in conservation practice - Croft, Catherine; MacDonald, Susan; Ostergren, Gail (Conserving modern heritage, 2018)
This volume brings together fourteen case studies that address the challenges of conserving the twentieth century's most ubiquitous building materia: concrete. Concrete: Case Studies in Conservation Practice is the first book in the Ghetty Conservation Institute's Conserving Modern Heritage series, which offers recent, thorough, and well-vetted case studies on conserving twentieth-century heritage. The projects selected represent a range of building typologies, uses and sizes, from the high-rise housing blocks of Le Corbusier's Unité d'habitation and public institutions such as the National Theatre in London to small monuments such as the structures at Dudley Zoological Gardens and a sculpture by Daniel Judd. The projects also represent a range of environmental and economic contexts. Some projects benefit from high levels of heritage protection and access to funding, while others have had to negotiate conservation with stringent cost limitations. All follow a rigorous conservation approach, beginning with a process of investigation and diagnosis to identify causes and target repairs, balanced with conservation requirements to preserve significance. Written by architects, engineers, conservators, scholars, and other professionals in the field, these detailed, well-illustrated studies demonstrate sound practice, rigorous methodology, and technological innovation and showcase the vibrancy of the field as it stands today.